PAAD. Person-focused analysis od architectural design. Architects need technical and humanistic approaches to be better understood and design architecture. This is why PAAD is born. - Llorca-Bofí, Josep (Technische Hochschule Ostwestfalen-Lippe, IDS Institut für Designstrategien, 2021)
The main task of PAAD is the study of the architectural design, with a focus on people’s perceptions, especially in situational contexts where sound matters. PAAD’s vision is person-focused, since architectural design covers different personal needs ranging from the basic safety needs, well-being and comfort, communication, to the religious experiences. Moreover, it is person-focused as long as it bridges the scientist ́s and architect’s knowledge through personal vocabularies. The visionary approach is to offer new knowledge about architect’s designs implications on people’s perception, by passing over the specific languages of other research areas, such as acoustics. It is the hope of PAAD that this knowledge will help the architects in their daily design practice and, in a long term period, improve people’s life in our cities.
Keywords: Architekturkonzept; Städtebaukonzept; Entwurfsauffassung; Raumwahrnehmung; Gebaute Umwelt; Wirkung; 3D-Modell; Photogrammetrie; Lärmschutz; Aufenthaltsqualität; Lebensqualität